Learning Creative Dance Through Audio Visual Media in Class XI MAN 1 Palembang - Talia Syahnia; Deria Sepdwiko; Efita Elvandari (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to determine the process of learning creative dance through audio-visual media in class XI MAN 1 Palembang. This study uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. The subjects of the study were art and culture teachers and class XI students of MAN 1 Palembang. The results of the study indicate that the use of audio-visual media can help students understand dance movements, increase learning interest, and make it easier for students to practice creative dance. The media used was a dance video displayed via mobile phone during the learning process. The teacher explained the material theoretically, then students watched the dance video and then practiced the dance movements in groups. The use of audio-visual media has a positive impact on learning because students become more active, enthusiastic, and easier to understand the material. In addition, audio-visual media helps teachers deliver material more interestingly and effectively. Based on the results of the study, it can be concluded that learning creative dance through audio-visual media in class XI MAN 1 Palembang went well and helped increase students' interest and understanding in learning dance.